Current economic impact on the Mayor bank from the implementation (2008) risk management system for money laundering and financing of terrorism SARLAFT (2014)
Throughout the history of man and the money has been the growing desire of getting rich quickly and easily which leads to the implementation of activities that are outside the legal parameters to achieve the goal. Now after achieving the ill-gotten resources which have the disadvantage of criminals is trying by any means to legalize money by trying through various methods of money laundering or assets enter the financial system this money and get benefits economic, reinvest in the criminal activities that generate or at other times by funding actions that may undermine the company or government entities.